On the analysis of the law of the iterated logarithm in open queueing networks. Issue 2 (3rd April 2019) - Minkevičius, Saulius
ABSTRACT: The modern queueing theory is one of the powerful tools for a quantitative and qualitative analysis of communication systems, computer networks, transportation systems, and many other technical systems. The paper is designated to the analysis of queueing systems, arising in the network theory and communications theory (called open queueing network). We have proved here the theorem on the law of the iterated logarithm (LIL) for the virtual waiting time of a job in an open queueing network under heavy and light traffic conditions. Also, the work presents a survey of papers for the virtual waiting time of a job in heavy traffic. Finally, we present an application of the proved theorems to the technical model from computer network practice.